Harnessing social media for business: case study of Zimbabwe. doc - Musungwini, Samuel; Zhou, Tinashe Gwendolyn; Zhou, Munyaradzi; Ruvinga, Caroline (2016)
The purpose of this research was to establish the impact of harnessing social media on the Zimbabwean businesses with particular reference to Facebook. The researchers looked at literature from other researchers to guide them. The researchers used focus group discussion and questionnaires to elicit information from the subjects. Participants to the questionnaire research were Facebook users that were actively running Facebook profiles mainly those participating on Zimbabwean business promotional campaigns on this social platform at the time of the research. On the focus group discussion participants were some of the MSc Information Systems Management students at Midlands State University. Although in Zimbabwe at the present moment social media is still evolving and its potential in business still remains to be seen. Social Media creates a real connection between companies and customers; that connection creates a trend for purchase intensity.